The Management Process of Grassroots Innovation that has Potentials for Commercialisation - Barbara, Anak Dieo (unimas, 2016)
The research was conducted to create the guidelines on managing grassroots innovation (GI) products for commercialisation. GI could be defined as a process that occurred due to study on problems of existing products and the needs for new innovation. The existence of GI was due to the needs and problems faced by the villagers or the grassroots communities. The process and activities of developing new products are made by the communities. The specific management strategies are needed to utilise the role of each expert in developing GI. The management process of GI is important to equip grassroots communities with important knowledge and skill in creating a good product for commercialisation. Collected data from reading, field observation, interview and questionnaires are compiled to create the best management process of GI. GI products with potential to be commercialised for this research is luffa fiber. The case study on luffa fiber was undertaken for this research. Through the case study, identified product was developed in design and function. The new product developed from the luffa fiber is shower sponge, oven mitt, dishwashing sponge and bottle cleaning brush. Product Design Specification (PDS) for the new develop products for case study is to serve people’s needs, aesthetically pleasing and multipurpose. The improved management process of GI was identified from the case study process of GI products.